Biological Control of Lettuce Drop and Host Plant Colonization by Rhizospheric and Endophytic Streptomycetes - Chen, Xiaoyulong; Pizzatti, Cristina; Bonaldi, Maria; Saracchi, Marco; Erlacher, Armin; Kunova, Andrea; Berg, Gabriele; Cortesi, Paolo (Frontiers in Microbiology, 2016)
Lettuce drop, caused by the soil borne pathogen Sclerotinia sclerotiorum, is one of the most common and serious diseases of lettuce worldwide. Increased concerns about the side effects of chemical pesticides have resulted in greater interest in developing biocontrol strategies against S. sclerotiorum. However, relatively little is known about the mechanisms of Streptomyces spp. as biological control agents against S. sclerotiorum on lettuce. Two Streptomyces isolates, S. exfoliatus FT05W and S. cyaneus ZEA17I, inhibit mycelial growth of Sclerotinia sclerotiorum by more than 75% in vitro. We evaluated their biocontrol activity against S. sclerotiorum in vivo, and compared them to Streptomyces lydicus WYEC 108, isolated from Actinovate®. When Streptomyces spp. (106 CFU/mL) were applied to S. sclerotiorum inoculated substrate in a growth chamber one week prior lettuce sowing, they significantly reduced the risk of lettuce drop disease, compared to the inoculated control. Interestingly, under field conditions, S. exfoliatus FT05W and S. cyaneus ZEA17I protected lettuce from drop by 40% and 10% respectively, whereas S. lydicus WYEC 108 did not show any protection. We further labeled S. exfoliatus FT05W and S. cyaneus ZEA17I with the enhanced GFP (EGFP) marker to investigate their rhizosphere competence and ability to colonize lettuce roots using confocal laser scanning microscopy (CLSM). The abundant colonization of young lettuce seedlings by both strains demonstrated Streptomyces’ capability to interact with the host from early stages of seed germination and root development. Moreover, the two strains were detected also on two-week-old roots, indicating their potential of long-term interactions with lettuce. Additionally, scanning electron microscopy (SEM) observations showed EGFP-S. exfoliatus FT05W endophytic colonization of lettuce root cortex tissues. Finally, we determined its viability and persistence in the rhizosphere and endorhiza up to three weeks by quantifying its concentration in these compartments. Based on these results we conclude that S. exfoliatus FT05W has high potential to be exploited in agriculture for managing soil borne diseases barely controlled by available plant protection products.